Structure, Dielectric, and Electrochemical Studies on Poly(Vinylidene Fluoride‐Co‐Hexafluoropropylene)/IonicLiquid 1‐Ethyl‐3‐Methylimidazolium Tricyanomethanide‐Based Polymer Electrolytes. Issue 7 (7th February 2022) - Kumar, Sushant; Singh, Pramod K.; Agarwal, Daksh; Singh Dhapola, Pawan; Sharma, Tejas; Savilov, Serguei V.; Arkhipova, Ekaterina A.; Singh, Manoj K.; Singh, Abhimanyu
Abstract : Solid polymer electrolyte films blended with ionic liquid 1‐ethyl‐3‐methylimidazolium tricyanomethanide (EMImTCM) and poly(vinylidene fluoride‐co‐hexafluoropropylene) (PVdF‐HFP) are prepared via solution cast technique. The physical characterization of polymeric film is performed by X‐ray diffraction (XRD), polarized optical microscopy (POM), Fourier transform infrared spectroscopy (FTIR), and thermo‐gravimetric analysis (TGA) studies. The gel electrolyte film with 300 wt% of IL shows the high ionic conductivity value of 3.7 × 10 −2  S cm −1, and operating voltage from −0.5 to 1.5 V, i.e., electrochemical stability window (ESW) ≈ 2.0 V. The dielectric properties of the polymeric films such as dielectric constant, dielectric loss tangent (Tan δ ), relaxation frequency, and time are evaluated. Abstract : Highly conducting, flexible ionic liquid‐doped solid polymer electrolyte films are prepared using a novel solution cast technique. Electrical, structural, and photoelectrochemical properties are enhanced drastically by doping ionic liquid, which confirms that ionic liquid could be a novel candidate to be treated as a dopant in developing high conducting electrolyte.